2003
DOI: 10.1097/01.lab.0000092231.54761.cd
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanisms of Gastric Adaptation to Aspirin-Induced Injury: A Role for Regenerating Protein but Not Trefoil Peptides

Abstract: SUMMARY:The phenomenon of reduced gastric mucosal injury despite repeated doses of a damaging agent is termed adaptation. Adaptation to nonsteroidal anti-inflammatory drug-induced injury has been clearly demonstrated in both humans and experimental animals; however, the precise mechanisms remain unclear. We hypothesized that mediators of adaptation might be the regenerating protein (RegI) and the trefoil peptides TFF1 and TFF2, because these proteins play pivotal roles in gastric mucosal protection and repair.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…There is still some potential for cross talk between these mechanisms. Aspirin-induced injury does not alter Tff1 or Tff2 mRNA and protein in rat stomach (117), but the more severe damage caused by repetitive administration of aspirin causes an increase of Tff2 and Tgfα (60). Indomethacin or aspirin also increases TFF2 mRNA (with no effect to TFF1 and TFF3 ) in MKN45 cell, a human gastric cancer cell line (118, 119).…”
Section: Trefoil Factor and Gastrointestinal Diseasesmentioning
confidence: 99%
“…There is still some potential for cross talk between these mechanisms. Aspirin-induced injury does not alter Tff1 or Tff2 mRNA and protein in rat stomach (117), but the more severe damage caused by repetitive administration of aspirin causes an increase of Tff2 and Tgfα (60). Indomethacin or aspirin also increases TFF2 mRNA (with no effect to TFF1 and TFF3 ) in MKN45 cell, a human gastric cancer cell line (118, 119).…”
Section: Trefoil Factor and Gastrointestinal Diseasesmentioning
confidence: 99%
“…Importantly, mouse Reg III was shown to be a Schwann cell mitogen that accompanies the regeneration of motor neurons (Livesey et al 1997), and Reg protein functions as a neurotrophic factor for motor neurons (Nishimune et al 2000). Reg was also shown to mediate gastric mucosal proliferation (Asahara et al 1996;Fukui et al 1998;Kazumori et al 2000;Alderman et al 2003) and vascular cell viability (Kiji et al 2003) in rats. The expression of Reg protein receptor mRNA has also been detected in liver, kidney, stomach, small intestine, colon, adrenal gland, pituitary gland, and brain , suggesting that the Reg-Reg receptor signal system is involved in a variety of cell types other than pancreatic β-cells.…”
Section: β β-Cell Regeneration and The Regenerating Genementioning
confidence: 99%
“…Koitabashi et al (26) reported Indometacin up-regulates TFF2 expression in gastric epithelial cell in vitro . Alderman et al (27) investigated relationship between TFF1 & TFF2 and adaptation to aspirin in gastric mucosa in vivo . They reported that quantification of TFF1 and TFF2 protein level in adapted group slightly were decreased (but no significant change) than that of control group.…”
Section: Discussionmentioning
confidence: 99%